PENGARUH E-PROCUREMENTTERHADAP TERWUJUDNYA GOOD GOVERNANCE - Rieska Maharani; Ardi Hamzah (Universitas Trunojoyo Madura, 2008)
The purpose of this research are to examine effect variablesabout e-procurement of good governance. The respondents of theresearch at Pemkot Surabaya. Purposive sampling technique is chosenwith criteria respondents at staff Pemkot Surabaya. Data has gatheredby questionnaires and documentation. Sample total is 66 respondent.The result of research with partial regression indicate that cognitivestyle significantly effect on result of effectiveness, efficiency,competitive, transparency, rule of law, and accountability. The resultof research with simultaneous regression indicate that perceptionabout effectiveness, efficiency, competitive, transparency, rule of law,and accountability . The value R2is 66,6% indicate that perceptionabout effectiveness, efficiency, competitive, transparency, rule of law,and accountability 66,6% on result of good governance, while 33,4%by other factors.